Social Media Dependency and Academic Achievement as Predictors of Learning Motivation: Ketergantungan Media Sosial dan Prestasi Akademik sebagai Prediktor Motivasi Belajar - Wicaksono, Vandy Akhmad; Eko Hardiansyah (Universitas Muhammadiyah Sidoarjo, 2025)
The objective of this study is to examine the influence of social media dependency and academic achievement on learning motivation among students at Al-Islam High School. The variables in this study include social media dependency and academic achievement as independent variables (X) and learning motivation as the dependent variable (Y). The researcher employed a quantitative research design using multiple regression analysis, with a sample of 289 students selected through proportionate stratified random sampling. The research instruments included adapted scales using the Likert model for learning motivation, online game addiction, and emotion regulation. The learning motivation scale was adapted from the Motivated Strategies for Learning Questionnaire (MSLQ) with a Cronbach's Alpha reliability of 0.840. The social media dependency scale was adapted from the Internet Addiction Scale (IAS) with a Cronbach's Alpha reliability of 0.862, and the academic achievement scale was adapted from the Learning Achievement Scale (LAS) with a Cronbach's Alpha reliability of 0.882. The results of the data analysis using multiple linear regression showed that the variables of social media dependency and academic achievement simultaneously have a significant effect on learning motivation, contributing 30.2% to the variance. Partial analysis indicated that social media dependency has a significant impact on learning motivation with a β value of -0.466 (p < .001), contributing 24.7% to the variance, while academic achievement also has a significant impact on learning motivation with a β value of 0.154 (p < .001), contributing 5.4% to the variance, indicating that social media dependency has a larger effect on learning motivation. Highlights: Significant Influence – Social media dependency and academic achievement together influence learning motivation, explaining 30.2% of the variance. Negative Impact of Social Media – Social media dependency negatively affects learning motivation (β = -0.466), contributing 24.7% to the variance, showing a stronger effect than academic achievement. Positive Role of Academic Achievement – Academic achievement positively influences learning motivation (β = 0.154), contributing 5.4% to the variance, but its effect is smaller compared to social media dependency. Keywords: Social Media Dependency, Academic Achievement, Learning Motivation